High Temperature Oxidation Behavior of T91 Steel in Dry and Humid Condition - Yonghao, Leong; Farah, Alia; Kurniawan, Tedi (The Language Center of Indonesia University of Education, 2016)
High temperature oxidation behavior of T91 ferritic/martensitic steel was examined over the temperature range of 500 to 700°C in dry and humid environments. The weight gain result revealed that oxidation occurs at all range of temperatures and its rate is accelerated by increasing the temperature. The weight gain of the oxidized steel at 700°C in steam condition was six times bigger than the dry oxidation.. SEM/EDX of the cross-sectional image showed that under dry condition, a protective and steady growth of the chromium oxide (Cr2O3) layer was formed on the steel with the thickness of 2.39±0.34 µm. Meanwhile for the humid environment, it is found that the iron oxide layer, which consists of the hematite (Fe2O3) and magnetite (Fe3O4) was formed as the outer scale, and spinnel as inner scale. This result indicated that the oxidation behavior of T91 steel was affected by its oxidation environment. The existence of water vapor in steam condition may prevent the formation of chromium oxide as protective layer.